2017
DOI: 10.1270/jsbbs.17007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of the <i>qSBN7</i> locus, a QTL controlling secondary branch number per panicle in rice

Abstract: Secondary branch number (SBN) is an important component affecting spikelet number per panicle (SPP) and yield in rice. During recurrent backcross breeding, four BC2F4 populations derived from the high-yield donor parent IR65598-112-2 and the recurrent parent Tainan 13 (a local japonica cultivar) showed discontinuous variations of SPP and SBN within populations. Genetic analysis of 92 BC2F4 individuals suggested that both SPP and SBN are controlled by a single recessive allele. Two parents and 37 BC2F4 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…To investigate the whole-genome background of BIL_TN13 sbn and BIL_TCS10 sbn , the RAD libraries of TN13, TCS10, IR65598-112-2, BIL_TN13 sbn and BIL_TCS10 sbn were constructed as previously described (Etter et al 2011). A total of 7.6 Gb raw reads were obtained on an Illumina HiSeq4000 at Tri-I Biotech Inc. (Taipei, Taiwan), and then analyze as previously described (Wang et al 2017b).…”
Section: Next-generation Sequencing and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the whole-genome background of BIL_TN13 sbn and BIL_TCS10 sbn , the RAD libraries of TN13, TCS10, IR65598-112-2, BIL_TN13 sbn and BIL_TCS10 sbn were constructed as previously described (Etter et al 2011). A total of 7.6 Gb raw reads were obtained on an Illumina HiSeq4000 at Tri-I Biotech Inc. (Taipei, Taiwan), and then analyze as previously described (Wang et al 2017b).…”
Section: Next-generation Sequencing and Sequence Analysismentioning
confidence: 99%
“…Grain number is associated with several morphological components of panicle architecture, among which secondary branch number per panicle is one of the most crucial (Mei et al 2006;Luo et al 2009). To identify new genes for grain number, a backcross population with segregating secondary branch number per panicle and grain number phenotypes was developed by using the donor parent IR65598-112-2 and recurrent parent TN13 (Wang et al 2017b). Genetic analysis and rough genetic mapping suggested that qSBN7, a single locus located on the long arm of chromosome 7, underlay the secondary branch and grain number variant and that the allele of IR65598-112-2 was recessive (Wang et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic maps are effective tools for finding, dissecting and modifying the genes that determine simple and sophisticated traits in crops [12]. Restriction-site association DNA (RAD) technique together with the NGS is a cost-effective method that can simultaneously detect thousands of SNPs [13], and has been used for integrating high-density linkage maps and genetic analysis in plants, such as rice [14], sunflower [15], wheat [16], grape [17] and soybean [1821]. Recently, genome-wide association study (GWAS) has become popular due to its high-resolution mapping when it was compared to conventional linkage mapping for dissecting complex genetic plant traits [22].…”
Section: Introductionmentioning
confidence: 99%
“…The trait that did not show any significant variation was panicle secondary branching. Panicle branching is one of the important architectural traits for breeders and agronomists (Thangasamy et al 2011) and secondary branch number is associated and affects spikelet number per panicle and final yield in rice (Wang et al 2017). Though the TRVs were characterized to have low to no diversity in most of the qualitative traits, desirable traits were also observed.…”
Section: Diversity Using Agromorphological Traitsmentioning
confidence: 99%